PENGARUH PENGGUNAAN MODEL PEMBELAJARAN DOMINO TEHADAP MOTIVASI BELAJAR PPKn SISWA KELAS X SMK LABOR PEKANBARU - Putri Mustika; Sri Erlinda; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the low motivation of learning PPKn students in SMK Labor Pekanbaru. The formulation of the problem in this research is " Is there any significant effect of using Domino learning modeltoward students’ motivation in learning PPKn atat SMK Labor Pekanbaru?". This study aims to determine the effect of of using Domino learning modeltoward students’ motivation in learning PPKn at SMK Labor Pekanbaru. This research was conducted at SMK Labor Pekanbaru in March 2018. This research was a quantitative descriptive study that was experimental.Population in this study were students of class X SMK Labor Pekanbaru. The sample in this research was taken based on "Random Sampling" technique. Where the class taken into the sample was the students of class X RPL (experimental class) who were given the domino learning model, and class X TKJ (control class) were students who were given the conventional method. Then data analysis by using homogeneity test and "t" test. Based on the result of research indicated that there wasan effect of learning motivation between student who using Domino learning model and conventional method in SMK Labor Pekanbaru ( > ).Where there was an average increase towardmotivation in learning PPKn of experimental class  from 30.92 to 33.84 and the average of PPKn learning motivation of control class from 20,82 to 20,14. Thus the hypothesis which reads that there is an effect of using Domino learning model toward learning motivation of PPKn student at SMK Labor Pekanbaru, can be accepted. Key Words : Effect, Domino, Motivation